Report on Quick Study of Pradhan Mantri Gram Sadak Yojana (PMGSY) - Planning Commission (Planning Commission, 2005)
In India, there are about more than 6 lakh villages located in different terrain conditions, e.g. plains, hilly and mountainous regions, deserts, swamps, coastal regions, backward areas, tribal pockets, etc. The climatic conditions also vary from place to place to a great extent. Social, economical and educational development of villages in these areas greatly depends on accessibility. A large number of villages in rural India are still not connected with the all weather roads. The employment opportunities and basic necessities like, health, education, etc. cannot reach rural masses without a system of good road network. It has now been realised that for the development of rural areas, development of proper road communication system must be a priority. The Primary objective of PMGSY is, therefore, to provide connectivity by way of all weather surfaced roads to the unconnected habitations in the rural areas in such a way that habitations with population of 1000 persons and above are covered by 2003 and habitations with population of 500 persons by the end of 2007.
Programme Evaluation Organisation Planning Commission Government of India New Delhi